2018
DOI: 10.1016/j.jretconser.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers perceived risk and trust for mobile shopping: A theoretical framework and empirical study

Abstract: Despite mobile device usage being at an all-time high, their utilisation for mobile shopping activities is inherently low. The study, first, identifies prominent areas of academic concern and examines areas requiring further insight. A theoretical model is developed to examine multi-faceted risk and trust effects on consumer adoption intention. Empirical results demonstrate several trust and risk perceptions as having varying effects on consumers' mshopping intention. Inclusion of age and gender reveals discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
152
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 132 publications
(315 reference statements)
5
152
2
9
Order By: Relevance
“…Kim et al [16] reported that trust can provide users with high expectations for their successful transactions, and they will use services with high satisfaction rates. Trust can positively influence customer intentions in various digital service contexts, such as e-commerce [16], internet banking [7], online social networks [17,18], mobile shopping [19,20], mobile banking [21,22], and mobile payments [23,24]. Fintech companies can simultaneously retain existing users and attract potential users if they supply a trustworthy environment in which users feel secure and are convinced their transactions are secure.…”
Section: Trust and Perceived Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [16] reported that trust can provide users with high expectations for their successful transactions, and they will use services with high satisfaction rates. Trust can positively influence customer intentions in various digital service contexts, such as e-commerce [16], internet banking [7], online social networks [17,18], mobile shopping [19,20], mobile banking [21,22], and mobile payments [23,24]. Fintech companies can simultaneously retain existing users and attract potential users if they supply a trustworthy environment in which users feel secure and are convinced their transactions are secure.…”
Section: Trust and Perceived Riskmentioning
confidence: 99%
“…Previous reports indicated that trust can reduce risks in e-commerce [16,25,26], internet banking [7], mobile shopping [19,27], mobile banking [28], and mobile payments [23,29]. Trust in financial transactions in particular can alleviate privacy and security concerns [30,31] as well as the risks associated with the opportunistic behavior of Fintech providers [19]. Trust is critical because trust drives Fintech-use behavior while reducing uncertainty and risk, and it has become a reliable strategy for effectively handling risky and uncertain financial transactions.…”
Section: Trust and Perceived Riskmentioning
confidence: 99%
“…Perceived risk is a multidimensional variable, including time, function, physical, financial, social and psychological risks [46]. Relevant studies have shown that perceived risk has a negative impact on consumers' attitude and intention to use innovative products or services [47][48][49]. The risk perception is very crucial as it could affect directly to the purchase and purchasing intention.…”
Section: Perceived Risk (Pr)mentioning
confidence: 99%
“…Consumers undergo financial frauds [11], deal with leaked personal and confidential information and becoming victim of the mendacious advertisements on the shopping websites by e-vendors. Product's performance risk is linked with the hazards associated with the non-functionality of the product [19][20] whereas financial risk is linked with unreliability conjoined with the monetary loss due to the security issue while making electronic payments or even product/service failure [21]. However, time risk in linked with the unnecessary difficulties or hindrances that a consumer experience while surfing website, placing orders, or waiting for the product delivery [22].…”
Section: A Perceived Riskmentioning
confidence: 99%